Extracts from the Cochrane Library: functional endoscopic balloon dilation of sinus ostia for chronic rhinosinusitis. - Burton, M; Bhattacharyya, N; Rosenfeld, R (2011)
The "Cochrane Corner" is a quarterly section in the Journal that highlights systematic reviews relevant to otolaryngology-head and neck surgery, with invited commentary to aid clinical decision making. This installment features a Cochrane Review, titled "Functional Endoscopic Balloon Dilation of Sinus Ostia for Chronic Rhinosinusitis," that finds no convincing evidence supporting balloon dilation compared to conventional surgical modalities for managing refractory disease.